The Effect of Renewable Energy Consumption on Sustainable Economic Development: Evidence from Emerging and Developing Economies - Mun Mun Ahmed (Energies, 2019)
The objective of the paper is to figure out the nexus between renewable energy consumption and sustainable economic development for emerging and developing countries. In this paper, a panel of 30 emerging and developing countries is selected using the World Development Indicators (WDI) of the World Bank, Renewable Energy Country Attractiveness Index (RECAI) by Ernst and Young, and a random selection method based on the current trend of renewable energy consumption for five different regions of the world i.e., Asia, South-Asia, Latin America, Africa and the Caribbean. To achieve the objective, robust panel econometric models such as the Pesaran cross-section dependence (CD) test, second generation panel unit root test, e.g., cross-sectional augmented IPS test (CIPS) proposed by Pesran (2007), panel co-integration test, fully modified ordinary least square (FMOLS) and dynamic ordinary least square (DOLS) are applied to check the cross-sectional dependence, heterogeneity and long-term relationship among variables. The panel is strongly balanced and the findings suggest a significant long-run relationship between renewable energy consumption and economic growth for selected South Asian, Asian and most of the African countries (Ghana, Tunisia, South Africa, Zimbabwe and Cameroon). But for the Latin American and the Caribbean countries, economic growth depends on non-renewable energy consumption. Renewable energy consumption in the selected countries of these two regions are still at the initial stage. In case of the renewable energy consumption and <semantics> CO 2 </semantics> emissions nexus, for selected South Asian, Asian, Latin American and African countries both GDP and non-renewable energy consumption cause the increase of <semantics> CO 2 </semantics> emissions. For the Caribbean countries only non-renewable energy consumption causes the increase of <semantics> CO 2 </semantics> emissions. An important finding regarding renewable energy consumption-economic growth nexus indicates the existence of bi-directional causality. This supports the existence of a feedback hypothesis for the emerging and developing economies. In the case of renewable energy consumption- <semantics> CO 2 </semantics> emissions nexus, there exists unidirectional causality. This supports the existence of the conservation hypothesis, where <semantics> CO 2 </semantics> emissions necessitates the renewable energy consumptions. Based on the findings, the study proposes possible policy options. The countries, who have passed the take-off stage of renewable energy consumption, can take advanced policy initiatives e.g., feed-in tariff, renewable portfolio standard and green certificate for long-term economic development. Other countries can undertake subsidy, low interest loan and market development to facilitate the renewable energy investments.